VERY HIGH SPEED HIGH POWER SEMICONDUCTOR SWITCH OFF CIRCUIT (Perner's Contacts, 2011)
High speed high power semiconductor switch off circuits (SOS) attract an increasing interest due to their perspective application in various high power switching circuits in control, feeding or VHF systems. In this paper we concentrate on a short pulse generator for electronic equipment EMC resistance testing against a short but a high energy pulse overloading. The generator circuit design is described and an analysis of a high voltage diode in the off switching regime and related problems are described.
Keywords: High speed switching; SOS; semiconductor diode modeling; circuit simulation; nanosecond pulse generation; electromagnetic impulse; electromagnetic compatibility; EMC; EMI